2019
DOI: 10.1155/2019/2657902
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Working Memory Training Improves Task Performance and Neural Efficiency in Multiple Sclerosis Patients and Healthy Controls

Abstract: Background/Objective. To explore the effectiveness of a specific working memory (WM) training program in MS patients and healthy controls (HC). Method. 29 MS patients and 29 matched HC were enrolled in the study. MS and HC were randomly split into two groups: nontraining groups (15HC/14 MS) and training groups (14 HC/15 MS). Training groups underwent adaptive n-back training (60 min/day; 4 days). Functional magnetic resonance imaging (fMRI) was used to monitor brain activity during n-back performance (conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Following WMT, several clusters of decreased activation in WM associated regions were observed, implying that the WMT group performed the WM task using fewer neural resources than the CG after training completion. In line with our results, long-term WMT as implemented here has often been associated with decreased activation in healthy young ( Schneiders et al , 2011 ; Clark et al , 2017 ) and elderly ( Brehmer et al , 2011 ; Miró-Padilla et al , 2019 ) as well as neurological non-Parkinson’s disease patients ( Aguirre et al , 2019 ). These findings all align with the neural efficacy idea, postulating that better or as in this case ‘trained’ cognitive performers need less neural resources in order to successfully complete a task ( Haier et al , 1988 ; Neubauer and Fink, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Following WMT, several clusters of decreased activation in WM associated regions were observed, implying that the WMT group performed the WM task using fewer neural resources than the CG after training completion. In line with our results, long-term WMT as implemented here has often been associated with decreased activation in healthy young ( Schneiders et al , 2011 ; Clark et al , 2017 ) and elderly ( Brehmer et al , 2011 ; Miró-Padilla et al , 2019 ) as well as neurological non-Parkinson’s disease patients ( Aguirre et al , 2019 ). These findings all align with the neural efficacy idea, postulating that better or as in this case ‘trained’ cognitive performers need less neural resources in order to successfully complete a task ( Haier et al , 1988 ; Neubauer and Fink, 2009 ).…”
Section: Discussionsupporting
confidence: 90%
“…Previously, cognitive training has been identified as a new route of non-pharmacological intervention to preserve or even improve cognitive function in Parkinson’s disease ( Leung et al , 2015 ; Glizer and MacDonald, 2016 ). However, the potential of focused interventions on cognitive domains specifically vulnerable in Parkinson’s disease—such as WM—is sparse, despite convincing evidence of working memory training (WMT) effects from healthy individuals ( Klingberg, 2010 ; Melby-Lervåg and Hulme, 2013 ; Karbach and Verhaeghen, 2014 ; Constantinidis and Klingberg, 2016 ) and brain-injured non-Parkinson’s disease populations ( Johansson and Tornmalm, 2012 ; Aguirre et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism has also been described in early stages of neurodegenerative diseases in which task performance is still comparable to agematched healthy controls (Trujillo et al, 2014;Gerrits et al, 2015;Audoin et al, 2003;Lopez-Gongora et al, 2015). Indeed, in a recent study, working memory CT showed similar task-related activity decrease in healthy adults and a population of early-stage cognitively healthy MS patients (Aguirre et al, 2019). Cognitive performance in MS and PD patients is, however, generally impaired (Bosboom, Stoffers, & Wolters, 2004;Chiaravalloti & DeLuca, 2008) and compensatory mechanisms as described above may at later disease stage no longer be sufficient for these patients.…”
Section: Discussionmentioning
confidence: 52%
“…The maintenance of an attentional focus to perform the ANT could also be related to working memory mechanisms [81][82][83] . Considering this link between the two processes, diverse studies have described working memory impairments in cognitive tasks in patients with MS [83][84][85] .…”
Section: Discussionmentioning
confidence: 99%